ANALISIS KINERJA BADAN PERMUSYAWARATAN DESA (BPD) DI KECAMATAN OBA UTARA KOTA TIDORE KEPULAUAN (Suatu Studi di Kecamatan Oba Utara Kota Tidore Kepulauan) - Katengar, Sintikce; Dengo, Salmin; Sondakh, Telly (Sam Ratulangi University, 2015)
ABSTRACT: As stipulated UU.No.32 PP.No.72 2004 and 2005 that the Village Consultative Body (BPD) is an element of governance village with village government, and function establishes the rules the village with the village head, supervise the implementation of regulations and decisions village heads, also serves and share their aspirations is intended to answer the question the extent to which performance of BPD in carrying out its functions and authority in the District of North Oba Tidore Islands.This study used qualitative methods. Informants in this study as many as 16 people were taken by purposive in four villages, the village Ampera, Galala, Gosale, and Bukit Durian, consisting of the village chief, chairman / member of BPD, chairman / LPM members and citizens. Instrument is the researcher's own research, collection using interview techniques. Data analysis with qualitative analysis techniques of Miles and Hubernann.The results showed: (1) The effectiveness of the implementation of the three functions and authority of the BPD generally been pretty good; (2) The level of efficiency of the implementation of the three functions and authority of BPD is already quite good (3) The level of responsiveness in the implementation of the functions and powers of the BPD has also been quite good; (4) The level of accountability in the implementation of the functions and authority of BPD has been quite good.Based on the results of these studies conclude that the performance of the Village Consultative Body in the District of North Oba in carrying out its functions and authority establishes the rules villages along the village chief, overseeing the implementation of regulations and rules the village head, and share their aspirations as well as society in general has been pretty good views of indicators of effectiveness, efficiency, responsiveness, and accountability.Based on the conclusion of the study, it can be put forward suggestions as follows: (1) To improve the quality of human resources performance of BPD and BPD leadership needs to be improved through training in the field of government management. (2) To improve the performance of BPD, the spirit and excitement of labor leaders and members of the BPD should be given adequate support. (3) To improve the performance of BPD BPD should be able to establish good cooperation and harmony with the Government of the Village and the Village Community Institution (LPM, and other PKK).Keywords: Performance, Village Consultative Body (BPD)